Pengaruh Kompetensi, Beban Kerja, Dan Budaya Organisasi Terhadap Kinerja Pegawai Di Direktorat Statistik Harga, Badan Pusat Statistik - Sunarsah, Siyam; Zaini, Zaman (Reformasi Administrasi, 2025)
In the VUCA Era (Volatility, Uncertainty, Complexity, and Ambiguity), Qualified workers who can deliver strong performance and benefit their organization are needed. According to HR management science, human resources are an organization's most valuable asset and need to be properly maintained. As a non-ministerial government institution whose primary duty is to supply the government and community with data, the Central Statistics Agency of the Republic of Indonesia (BPS RI) must keep enhancing its operations to ensure that the data it produces is of ever-higher quality. One way to do this is by raising employee performance standards. The goal of this research is to examine and assess how competence, workload, and organizational culture affect workers' performance at the Central Statistics Agency (BPS) of the Republic of Indonesia's Directorate of Price Statistics. This study, which was carried out on 58 current employees of the BPS Directorate of Price Statistics, is quantitative in nature. Multiple linear regression, correlation, and descriptive analysis are all used in the analysis. The findings demonstrate that organizational culture, workload, and competence all significantly and favorably affect worker performance. In parallel, it is also known that competence, workload, and culture have a positive and significant influence of 55.6 percent, with other variables not included in this study having an influence on the remaining 44.4 percent.